2003
DOI: 10.1017/s0007087403005065
|View full text |Cite
|
Sign up to set email alerts
|

M. du Bois-Reymond goes to Paris

Abstract: This article examines the science of electrophysiology developed by Emil du BoisReymond in Berlin in the 1840s. In it I recount his major findings, the most significant being his proof of the electrical nature of nerve signals. Du Bois-Reymond also went on to detect this same ' negative variation', or action current, in live human subjects. In 1850 he travelled to Paris to defend this startling claim. The essay concludes with a discussion of why his demonstration failed to convince his hosts at the French Acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 2 publications
0
16
0
1
Order By: Relevance
“…Potentially, strong interactions might drive an electron system towards ferromagnetic instability [4]. Moreover, it has been suggested that the 'metallic' behavior in 2D is accompanied by a tendency to a ferromagnetic instability [12]. Thus, in relation to the still open question of the origin of the 2D MIT, direct measurements of these quantities in the dilute regime near the 2D MIT are crucial.…”
mentioning
confidence: 99%
“…Potentially, strong interactions might drive an electron system towards ferromagnetic instability [4]. Moreover, it has been suggested that the 'metallic' behavior in 2D is accompanied by a tendency to a ferromagnetic instability [12]. Thus, in relation to the still open question of the origin of the 2D MIT, direct measurements of these quantities in the dilute regime near the 2D MIT are crucial.…”
mentioning
confidence: 99%
“…Like the Academy of Sciences, the Academy of Medicine served as a jury of peers (functioning through appointed committees) to judge medical/ surgical innovations of both a theoretical and practical nature. For example, in a recent article we learn that du Bois-Reymond traveled from Berlin to Paris in 1849 to present his physiological research to the Academy of Sciences (Finkelstein 2003). And Weisz has described how new surgical/therapeutic procedures were demonstrated at the Academy of Medicine for approval from its members (Weisz 1995).…”
Section: The Nature and Purpose Of Academic Debatementioning
confidence: 99%
“…Paris was undisputed as the European center of science and medicine up to the mid-1830s, but for many scientists, such as the German physiologist Emil du-Bois-Reymond, Paris still held this position at mid-century (Finkelstein 2003). No other city, no other academies besides the Paris Academy of Medicine and the Paris Academy of Sciences could claim as much.…”
mentioning
confidence: 99%
“…Properly quantified (and quantized) action potentials are, in the practices I describe, cor-3. What are now called "action potentials" were first called "negative oscillations" ("negative Schwankung") in 1872 by Emil du Bois-Reymond (see Finkelstein 2003). Julius Bernstein, a student of du Bois-Reymond (as well as of Helmholtz), in 1902 proposed an early theory of how these pulses worked (Schuetze 1983).…”
mentioning
confidence: 99%